Influence of Yohimbe on blood parameters and Intestinal morphometry of broiler chickens - Olusola Obajuluwa (Universitas Airlangga, 2026)
Pausinystalia yohimbe was investigated for its effects on the gut health and blood profile of broiler chickens. A study involving 225 chickens fed a basal diet or a diet supplemented with a larvicide or varying doses of yohimbe (240, 300, or 360 mg/kg) was conducted. At 56 days old, blood and intestinal tissue samples were collected. The results showed that the diets had no significant effect on PCV, Hb, RBC, and WBC. However, at the starter phase, chickens fed 360 mg/kg of yohimbe had significantly higher (p<0.05) eosinophil counts. Supplementation with 240 mg/kg of yohimbe led to significantly higher (p<0.05) levels of total protein, albumin, globulin, and uric acid. In the finisher phase, the 360 mg/kg group showed significantly higher (p<0.05) total protein, albumin, and alanine aminotransferase (ALT). Also, chickens fed 240 mg/kg of yohimbe showed the best results for duodenal villi height and crypt depth. The 300 mg/kg group showed the highest (p<0.05) jejunum villi height and a significant increase in ileum villi height and crypt depth. In conclusion, supplementation with yohimbe at 240 mg/kg is recommended for improved blood and intestinal health in the starter phase, while 300 mg/kg is most effective for the finisher phase.